2011
DOI: 10.1523/jneurosci.4055-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

The Neuronal Basis of Long-Term Sensorimotor Learning

Abstract: The brain has a remarkable ability to learn and adjust behavior. For instance, the brain can adjust muscle activation to cope with changes in the environment. However, the neuronal mechanisms behind this adaptation are not clear. To address this fundamental question, this study examines the neuronal basis of long-term sensorimotor learning by recording neuronal activity in the primary motor cortex of monkeys during a long-term adaptation to a force-field perturbation. For 5 consecutive days, the same perturbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 51 publications
6
24
0
Order By: Relevance
“…There is consistent evidence from animal and human studies that M1 plays a central role in the long-term retention of motor skills following multisession training (Mandelblat-Cerf et al, 2011;Matsuzaka, Picard, & Strick, 2007;Floyer-Lea & Matthews, 2005;Kleim et al, 2004;Penhune & Doyon, 2002;Karni et al, 1995Karni et al, , 1998Kleim, Barbay, & Nudo, 1998;Nudo, Milliken, Jenkins, & Merzenich, 1996). Moreover, it has been recently shown that extended practice of the motor skill stabilizes the M1 activity pattern (Huang et al, 2013) and is associated with reduced metabolic activity in M1 (Picard, Matsuzaka, & Strick, 2013).…”
Section: Discussionmentioning
confidence: 87%
“…There is consistent evidence from animal and human studies that M1 plays a central role in the long-term retention of motor skills following multisession training (Mandelblat-Cerf et al, 2011;Matsuzaka, Picard, & Strick, 2007;Floyer-Lea & Matthews, 2005;Kleim et al, 2004;Penhune & Doyon, 2002;Karni et al, 1995Karni et al, , 1998Kleim, Barbay, & Nudo, 1998;Nudo, Milliken, Jenkins, & Merzenich, 1996). Moreover, it has been recently shown that extended practice of the motor skill stabilizes the M1 activity pattern (Huang et al, 2013) and is associated with reduced metabolic activity in M1 (Picard, Matsuzaka, & Strick, 2013).…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, we also expressed M1 activity in terms of the dynamics of the “motor plan”, using an approach developed by Mandelblat-Cerf, et al (Mandelblat-Cerf et al 2011). Briefly, during the window between movement onset and peak speed, we used endpoint velocity to compute the underlying CF force, which we subtracted from the force recorded by the force transducer.…”
Section: Resultsmentioning
confidence: 99%
“…The Arce et al paradigm of one-direction force-field learning was recently used, in conjunction with chronic recording arrays, to study correlates of long-term adaptation across five daily sessions (Mandelblat-Cerf et al 2011). Although recordings of the same neurons across sessions were not specifically sought out or analyzed, the chronic ensemble results of Mandelblat-Cerf et al are certainly relevant to our study.…”
Section: Discussionmentioning
confidence: 99%